IMPLEMENTASI GOOD GOVERNANCE PADA MALL PELAYANAN PUBLIK PEMERINTAH KOTA BOGOR : - Wisarini, Bintari Ruranti; Zainal, Veithzal Rivai; Hakim, Azis (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
This research explores the implementation of Good Governance principles in the Public Service Mall (MPP) application in the Government of Bogor City. Data collection was conducted by distributing questionnaires to 50 respondents. The results of the data analysis using multiple linear regression reveal interesting findings related to the factors influencing the usage of the MPP in the context of local government. The research findings indicate that transparency and accountability have a significant impact on the intensity of MPP usage. Transparency plays a crucial role in fostering trust and efficiency in public administration. Citizens feel confident because the application provides comprehensive and accurate information, offering a transparent view of public service processes. Accountability has also been proven to influence MPP usage. Financial information, compliance, and government reporting within the application motivate users. When the government adheres to strong accountability principles, people are more likely to feel confident and motivated to interact with the application. However, another interesting finding is that legal certainty does not have a significant impact on the intensity of MPP usage. The application focuses on innovation and the efficiency of public services, making legal factors less crucial in determining its usage. As a recommendation, this research suggests the need for enhancing the information presented in the application and providing regular training to users. This is aimed at maintaining the sustainability and success of the MPP application's implementation within the context of Good Governance in Bogor City. Consequently, the MPP application can continue to provide maximum benefits to both the public and local government. Keywords: good governance; transparency; accountability; rule of law; public service mall.